A Novel and Highly Selective Epidermal Growth Factor Receptor Inhibitor, SMUZ106, for the Treatment of Glioblastoma - Ying Jiang; Chunhui Huang; Yaqi Huang; Lifan Long; Guowu Wu; Fengqiu Guo; Chuan Huang; Siming Liu; Zhengguang Zhu; Shaoyu Wu; Zhonghuang Li; Jiajie Zhang; et al. (MDPI AG, 2023)
Targeting the epidermal growth factor receptor (EGFR) is one of the potential ways to treat glioblastoma (GBM). In this study, we investigate the anti-GBM tumor effects of the EGFR inhibitor SMUZ106 in both in vitro and in vivo conditions. The effects of SMUZ106 on the growth and proliferation of GBM cells were explored through MTT and clone formation experiments. Additionally, flow cytometry experiments were conducted to study the effects of SMUZ106 on the cell cycle and apoptosis of GBM cells. The inhibitory activity and selectivity of SMUZ106 to the EGFR protein were proved by Western blotting, molecular docking, and kinase spectrum screening methods. We also conducted a pharmacokinetic analysis of SMUZ106 hydrochloride following i.v. or p.o. administration to mice and assessed the acute toxicity level of SMUZ106 hydrochloride following p.o. administration to mice. Subcutaneous and orthotopic xenograft models of U87MG-EGFRvIII cells were established to assess the antitumor activity of SMUZ106 hydrochloride in vivo. SMUZ106 could inhibit the growth and proliferation of GBM cells, especially for the U87MG-EGFRvIII cells with a mean IC50 value of 4.36 μM. Western blotting analyses showed that compound SMUZ106 inhibits the level of EGFR phosphorylation in GBM cells. It was also shown that SMUZ106 targets EGFR and presents high selectivity. In vivo, the absolute bioavailability of SMUZ106 hydrochloride was 51.97%, and its LD50 exceeded 5000 mg/kg. SMUZ106 hydrochloride significantly inhibited GBM growth in vivo. Furthermore, SMUZ106 inhibited the activity of U87MG-resistant cells induced by temozolomide (TMZ) (IC50: 7.86 μM). These results suggest that SMUZ106 hydrochloride has the potential to be used as a treatment method for GBM as an EGFR inhibitor.